Trends in the market of wine - Štrbac, Maja; Radojević, Velimir; Bogdanović, Borivoje (Economics of Agriculture, 2010)
The market of wine depends on many factors (supply, demand, production conditions, environmental conditions, technical equipment, etc.). The fall in prices of wine was to stimulate consumption. The last process is a market adjustment and it rather that fall of wine prices are automatically accompanied with the consumption grow. Given that the European Union is the most important wine market in the world, the paper described the EU wine market, consumption, market segmentation, production, trends, imports, exports, with emphasis on the opportunities and threats for exporters and producers in developing countries.